Increased mortality with resuscitative endovascular balloon occlusion of the aorta only mitigated by strong unmeasured confounding: An expanded analysis using the National Trauma Data Bank. Issue 5 (November 2021) - Linderman, George C.; Lin, Winston; Becher, Robert D.; Maung, Adrian A.; Bhattacharya, Bishwajit; Davis, Kimberly A.; Schuster, Kevin M.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is being increasingly adopted to manage noncompressible torso hemorrhage, but a recent analysis of the 2015 to 2016 Trauma Quality Improvement Project (TQIP) data set showed that placement of REBOA was associated with higher rates of death, lower extremity amputation, and acute kidney injury (AKI). We expand this analysis by including the 2017 data set, quantifying the potential role of residual confounding, and distinguishing between traumatic and ischemic lower extremity amputation. METHODS: This retrospective study used the 2015 to 2017 TQIP database and included patients older than 18 years, with signs of life on arrival, who had no aortic injury and were not transferred. Resuscitative endovascular balloon occlusions of the aorta placed after 2 hours were excluded. We adjusted for baseline variables using propensity scores with inverse probability of treatment weighting. A sensitivity analysis was then conducted to determine the strength of an unmeasured confounder (e.g., unmeasured shock severity/response to resuscitation) that could explain the effect on mortality. Finally, lower extremity injury patterns of patients undergoing REBOA were inspected to distinguish amputation indicated for traumatic injury from complications of REBOA placement. RESULTS: Of 1, 392, 482 patients meeting the inclusion criteria, 187 underwent REBOA. After inverse probability of treatment weighting, all covariates were balanced. The risk difference for mortality was 0.21 (0.14–0.29) and for AKI was 0.041 (−0.007 to 0.089). For the mortality effect to be explained by an unmeasured confounder, it would need to be stronger than any observed in terms of its relationship with mortality and with REBOA placement. Eleven REBOA patients underwent lower extremity amputation; however, they all suffered severe traumatic injury to the lower extremity. CONCLUSION: There is no evidence in the TQIP data set to suggest that REBOA causes amputation, and the evidence for its effect on AKI is considerably weaker than previously reported. The increased mortality effect of REBOA is confirmed and could only be nullified by a potent confounder. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.